Pengungkapan Tanggung Jawab Sosial dan Nilai Perusahaan: Dari Sudut Pandang Teori Akuntansi Positif dan Corporate Governance - Agustina Agustina; Sulia Sulia; Rice Rice (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study examine the influence of bonus plan hypothesis, debt/equity hypothesis, political cost hypothesis, earning management, institutional ownership, public ownership, independent board and audit committee on firm value with corporate social responsibility as the intervening variable. The study population is 65 natural resource companies listed in Indonesia Stock Exchange period 2012-2015. Based on purposive sampling method, 21 natural resource companies were selected (or 84 observations). Data was selected from the companies’ financial reports and analysed by using path analysis. This study found that corporate social responsibility can be used as an intervening variable to mediate the effect of political cost hypothesis, earning management, and audit committee to firm value. But, it cannot mediate the effect of bonus plan hypothesis, debt/equity hypothesis, institutional ownership, public ownership and independent board to firm value.